"He Wanted Me to Achieve that for Our Family and I Did, Too": Exploring First-Generation Students' Experiences of Turning Points During the Transition to College. Issue 2 (3rd April 2017) - Wang, Tiffany R.; Nuru, Audra K.
ABSTRACT: This study explored the ways in which family communication facilitated support and persistence for first-generation students during the transition from high school through the first year of college with a specific focus on the first-year experience, a pivotal time when first-generation students often decide whether they will leave or stay in college. Through semistructured interviews, we identified the communication events that first-generation students perceived to be turning points in their interpersonal interactions with their family members. Seventeen participants identified a total of 121 turning points that they experienced from family members spanning from the time they had their first conversation about going to college through the first year of college. Interviews revealed three suprathemes of turning points: (a) coauthoring the dream, (b) experiencing obstacles to the dream, and (c) actualizing the dream.